2011
DOI: 10.1111/j.1600-0412.2011.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the clinical use of the levonorgestrel‐releasing intrauterine system

Abstract: This overview focuses on recent developments in the clinical use of the levonorgestrel- releasing intrauterine system (LNG-IUS) on established indications. Recent studies confirm that the LNG-IUS is safe and equally effective for all age groups of women. All available studies showed that intrauterine contraception is more effective when compared to non-intrauterine contraceptive methods to prevent repeat abortions. Furthermore, insertion in young nulliparous women is acceptable in the majority of women and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 81 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…An understanding of the impact of contraceptive methods on the sexuality and health of both parties is needed (e.g. a vasectomy vs a levonorgestrel‐releasing IUD, which is reversible and simultaneously treats heavy menstrual bleeding) …”
Section: Resultsmentioning
confidence: 99%
“…An understanding of the impact of contraceptive methods on the sexuality and health of both parties is needed (e.g. a vasectomy vs a levonorgestrel‐releasing IUD, which is reversible and simultaneously treats heavy menstrual bleeding) …”
Section: Resultsmentioning
confidence: 99%
“…1 Many authorities [2][3][4][5][6] have supported use of intrauterine contraceptives in nulliparous women; however, a recent survey demonstrated that more than 60% of U.S. clinicians only infrequently offer intrauterine contraceptives to nulliparous women. This has been the result of its safety, convenience, and its effectiveness as a contraceptive and as a treatment for heavy menstrual bleeding.…”
mentioning
confidence: 99%
“…Previous studies have found that use of LARC after an abortion leads to a greater reduction in the risk of further unintended pregnancies and repeat abortions compared with use of other contraceptive methods. Few studies have included choice and use of subdermal implants post‐abortion and studies with longer follow‐up time are lacking . A high initial cost for levonorgestrel intrauterine systems (LNG‐IUS) and subdermal implants is, however, a challenge affecting the choice of contraceptive method .…”
Section: Introductionmentioning
confidence: 99%